2014
DOI: 10.1371/journal.pone.0101493
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HIV-Hepatitis C Co-Infection on Bone Mineral Density and Fracture: A Meta-Analysis

Abstract: ObjectiveThere is a variable body of evidence on adverse bone outcomes in HIV patients co-infected with hepatitis C virus (HCV). We examined the association of HIV/HCV co-infection on osteoporosis or osteopenia (reduced bone mineral density; BMD) and fracture.DesignSystematic review and random effects meta-analyses.MethodsA systematic literature search was conducted for articles published in English up to 1 April 2013. All studies reporting either BMD (g/cm2, or as a T-score) or incident fractures in HIV/HCV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Coinfection with hepatitis B and C was low. Two recent reviews have shown that the prevalence of low BMD and the risk of fracture are higher in hepatitis C-HIV coinfected patients than in HIV mono-infected controls [14,15], reflecting probably additional risk factors of osteoporosis associated with hepatitis C infection. Despite the exclusion of men treated for osteoporosis, optimization of vitamin D levels and low rate of coinfection with hepatitis B and C, we detected lower total vBMD at distal radius and tibia (16 and 14.3%, respectively) in HIV-positive men.…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with hepatitis B and C was low. Two recent reviews have shown that the prevalence of low BMD and the risk of fracture are higher in hepatitis C-HIV coinfected patients than in HIV mono-infected controls [14,15], reflecting probably additional risk factors of osteoporosis associated with hepatitis C infection. Despite the exclusion of men treated for osteoporosis, optimization of vitamin D levels and low rate of coinfection with hepatitis B and C, we detected lower total vBMD at distal radius and tibia (16 and 14.3%, respectively) in HIV-positive men.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of liver- and non-liver-related complications of chronic HCV infection are higher among HIV/HCV co-infected patients than HCV mono-infected patients [11,12]. In addition to its ability to induce liver fibrosis, chronic HCV infection is also associated with extra-hepatic complications, particularly abnormalities in bone metabolism and increased fracture risk, that may contribute to morbidity among HIV/HCV co-infected patients as this group ages [2,6,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Traditional risk factors for low BMD, including low body mass index (BMI), smoking, hypogonadism or menopause, and corticosteroid use are highly prevalent among HIV-infected individuals [12, 2629]. However, individuals with HIV experience BMD loss beyond what would be expected from these traditional risk factors alone [30], and there is evidence that both the HIV virus itself, and treatment with cART, contribute to ongoing bone loss in the HIV population.…”
Section: Proposed Mechanisms Of Hiv-associated Bone Lossmentioning
confidence: 99%